The Effect of CARTER Model on Customer Satisfaction Towards Loyalty: An Investigation on Muslim Customers of Islamic Banks in Bangladesh - Haque, Ahasanul; Chowdhury, Naila; Uddin, Bashir; Islam, Md Asadul; Kabir, Sardar Md Humayun (International Finance and Banking, 2024)
The objective of this study was to investigate the effects of CARTER model on customer satisfaction towards loyalty among Muslim customers of Islamic banks in Bangladesh. Initially, a theoretical model was established based on detailed literature review. Afterwards, a self-administered structured questionnaire was developed, and data were collected from 254 Muslim customers of Islamic banks in Bangladesh using purposive sampling technique. The collected data were later analyzed through EFA. Structural Equation Modelling (SEM) technique was performed to verify the model of the study and testing the hypotheses. The findings of the study revealed that compliance with Shariah, assurance, reliability, tangibility, empathy, and responsiveness are significant factors for customer satisfaction and also customer satisfaction was integral for attaining customer loyalty. The study focused on Islamic banking customers only from two of the largest cities in the country, particularly, Dhaka and Chittagong. This, in turn, opens the door for future researchers to contribute to this area of research through employing a larger sample and extending the current model through the incorporation of new variables. The study will be a meaningful addition to the literature of service quality, customer satisfaction and loyalty, particularly in the setting of Islamic banking in Bangladesh. This study has taken the initiative for identifying the underlying factors that would facilitate Islamic banks in satisfying their customers better and building customer loyalty.